Psychiatric disorders and mental health care among incarcerated men: A prerelease cross-sectional study in France - Thomas Fovet; Kevin D’Ovidio; Marion Eck; Imane Benradia; Stéphane Duhem; Camille Lancelevée; Pierre Thomas; Marielle Wathelet; Ali Amad (European Psychiatry)
Abstract